Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 304600 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Falco peregrinus Tunstall, 1771" ] } The dataset includes 304600 records from 418 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0004090-150410134957023/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences